2003
DOI: 10.1053/jhep.2003.50300
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Rinse: A Simple Protectant Against the Rat Liver Graft Injury Mimicking Heme Oxygenase-1 Preconditioning

Abstract: Heme oxygenase (HO)-1 preconditioning through genetic or pharmacologic interventions was shown experimentally to improve posttransplant outcome of liver grafts. However, its clinical application requires careful consideration because of the complexity and economic costs of the procedures. This study aimed to examine if graft preconditioning with HO-1 could be substituted by a simple treatment with heme-degrading products such as bilirubin. Rats were pretreated with or without hemin, an HO-1 inducer for precond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 35 publications
3
73
1
2
Order By: Relevance
“…5,18 Our previous study in rats suggested that another HO-derived product bilirubin but not CO has the ability to improve bile acid-dependent bile output of the post-cold ischemic liver grafts through its antioxidative action. 32 However, such an effect of bilirubin appears to be distinct from the stimulatory action of CO on biliary fluid excretion indicated in the current study. CO has been shown to exert diverse actions on biliary function through multiple mechanisms: First, stress-inducible levels of CO have the ability to elongate the intervals of bile canalicular contraction, which helps increase the stroke volume for promoting bile excretion; this process appears to involve mechanisms mediated by modulation of cytochrome P450 epoxygenases and intra- cellular Ca 2ϩ mobilization.…”
Section: Discussioncontrasting
confidence: 59%
“…5,18 Our previous study in rats suggested that another HO-derived product bilirubin but not CO has the ability to improve bile acid-dependent bile output of the post-cold ischemic liver grafts through its antioxidative action. 32 However, such an effect of bilirubin appears to be distinct from the stimulatory action of CO on biliary fluid excretion indicated in the current study. CO has been shown to exert diverse actions on biliary function through multiple mechanisms: First, stress-inducible levels of CO have the ability to elongate the intervals of bile canalicular contraction, which helps increase the stroke volume for promoting bile excretion; this process appears to involve mechanisms mediated by modulation of cytochrome P450 epoxygenases and intra- cellular Ca 2ϩ mobilization.…”
Section: Discussioncontrasting
confidence: 59%
“…21 Recently it has been shown that BV therapy blocked hepatic acetaminophen-induced injury in rats by protecting the liver against reactive oxygen and nitrogen intermediates. 22 Kato et al 23 have shown that BR rinse of livers decreased the oxidative stress and hepatobiliary dysfunction, mimicking the effects of HO-1-mediated preconditioning. In this report, BR used to rinse the grafts at a dose of 50 mol/L resulted in a mortality rate of 100%.…”
Section: Discussionmentioning
confidence: 95%
“…70 Bilirubin had a protective effect on the transplanted liver grafts via inhibition of lipid peroxidation in hepatocytes. 71 Although reduced iron (Fe 2 þ ) released by HO-1 from the core of the heme molecule is a potent prooxidant, the potential catalysis of oxidative reactions by this compound is limited through its chelation by iron-sequestering protein ferritin as well as via its active removal from the cell by the specific Fe-ATPase pump. 72 Moreover, ferritin production and biological activity of Fe-ATPase pump are potentiated by increased free iron in the intracellular pool due to enhanced HO-1 expression.…”
Section: Expression Of Il-6 After To Administration and Its Possible mentioning
confidence: 99%